Dynamic strain propagation in nanoparticulate zirconia refractory. (1st April 2015) - Jones, Morgan E.; Fearn, Steve; Winter, Rudolf; Yuan, Fajin; Lennie, Alistair R.; Parker, Julia E.; Thompson, Stephen P.; Tang, Chiu C.
<x xml:space="preserve">Abstract</x> Residual and intrinsic strains in granular materials have been studied extensively. However, understanding the dynamic strains that cause these resultant residual strains is key to developing better strain‐resistant materials. This investigation demonstrates a method for characterizing dynamic strain propagation in granular materials. The specimen is a zirconia‐based refractory composed of sol–gel‐derived zirconia nanoparticles in a potassium silicate glass binder. In situ synchrotron X‐ray powder diffraction in flat‐plate geometry is used to characterize the sample structure on timescales of the order of 1 ms. A 125 W CO2 laser is used to strain the sample with a 25 ms pulse length. To compensate for the poor flux on this timescale, a pump–probe method is repeated 1000 times and the resulting data are subsequently re‐binned to improve statistics. A Gaussian weighting function is also used to introduce better contrast between strained and unstrained frames. TOPAS Academic is used for fitting with a Le Bail model in `batch mode'. Lattice parameters and sample height are refined during fitting, along with a Lorentzian line width for extracting microstrain broadening. Microstrains, ɛ, in the range of 1.01 < ɛ < 1.46% are reported on a 1 ms timescale.